Mediators of invasions in the sea: life history strategies and dispersal vectors facilitating global sea anemone introductions - Glon, Heather; Daly, Marymegan; Carlton, James T.; Flenniken, Megan M.; Currimjee, Zara (Biological invasions, 2020)
Widespread non-native species tend to demonstrate an apparent lack of selectivity in habitat requirements, feeding regimes, and reproductive needs, while displaying a tendency to thrive in human-modified habitats. The high phenotypic plasticity typical of sessile, substrate-attached marine species may enhance their chances of survival and spread in a new region. Anthropogenic activities have changed marine habitats over a wide range of phenomena, including water temperature, community species composition, and the types of available substrates, creating new physical and biotic regimes that may contribute to the potential for successful species introduction. Here we examine ten species of sea anemones that have been introduced outside of their native range, and elucidate specific characteristics that are common among globally introduced sea anemones. Various life history strategies enable these species to survive and flourish through transport, introduction, establishment and spread, leading to the successful colonization of a new geographic area. Considering life history strategies and weighing of vector potential, we suggest conditions that facilitate introduction of these species, and identify species of sea anemones that may be introduced in the future in the face of changing climate and increased anthropogenic activities.